The sexual satisfaction of women after labour — part I - Stadnicka, Grażyna; Łepecka-Klusek, Celina; Pilewska-Kozak, Anna; Pawłowska-Muc, Agnieszka (Nursing Problems / Problemy Pielęgniarstwa, 2015)
Introduction/Aim. It is the aim of this research to assess the feelings and the thoughts expressed by women after labour towards their sexual activity. Material and methods. Research has been carried out amongst 360 women in the period of 3-6 months after labour. The survey questionnaire (Sexual Quality of Life Questionnaire Female) has been used in the research. The statistical analysis has been carried out with the help of the computer software IBM SPSS Statistics version 21. Results. The sexual satisfaction in the research group was found to be high and equalled M = 75.47 ± 24.68. More than half of the research participants (n = 192; 54.12%) assess their sexual activity positively. Every second (180; 50.00%) respondents were closely connected with your partner. Conclusions. The level of the experienced satisfaction with one’s sexual life expressed through feelings and thoughts of the women after labour is a diversified. The quality of sexual life assessed the most women after childbirth as good or very good.